HYPOGONADAL SYMPTOMS AND SEXUAL DYSFUNCTION AMONG MALES WITH T2DM - Kang, WH; Siruhan, M; Shree, VN; Karupiah, M; Sukor, N; Kamaruddin, NA (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Previous literature has reported hypogonadism and erectile dysfunction to be prevalent among males with type 2 diabetes mellitus (T2DM). The hypogonadism can be attributed to obesity and insulin resistance, while erectile dysfunction can be due to low testosterone levels as well as endothelial dysfunction in the microvasculature. There is paucity of data on the common hypogonadal symptoms as well as sexual function among Malaysian males with T2DM. METHODOLOGY We analysed the hypogonadal symptoms and sexual function of 63 males with T2DM and hypogonadism (defined as total testosterone <12 nmol/L and repeated free testosterone <0.255 nmol/L with Aging Male Symptoms (AMS) score ≥27) and 58 weight- and HbA1c-matched males with T2DM with normal testosterone levels. Two validated questionnaires were utilised: the AMS questionnaire for hypogonadal symptoms, and the International Index of Erectile Function-5 (IIEF-5) questionnaires for sexual function. The AMS questionnaire assesses 3 components, namely somato-vegetative, psychological symptoms and sexual symptoms. RESULTS Sexual symptoms were more common than somatovegetative or psychological symptoms, with 76.2% of hypogonadal males having severe sexual symptoms. 82.5% of hypogonadal males had reduced sexual ability, 68.3% had reduced morning erections and 25.4% had reduced libido. Among the 47.6% sexually active hypogonadal males, 37.9% had moderate to severe ED symptoms. 57.1% had severe to extremely severe decreased beard growth, 50.8% had felt burnt out while 17.5% complained of severe to extremely severe anxiety and 23.8% had irritability symptoms. CONCLUSION Sexual complaints, predominantly reduced sexual ability are more prevalent among males with T2DM and hypogonadism. Despite the low testosterone levels, most still have intact libido. Hence, males with T2DM should be actively screened for sexual symptoms and treated accordingly for better sexual quality of life. Somato-vegetative and psychological symptoms are not useful indicators for hypogonadism among males with T2DM.